((( - De Francesco, Alessandro (punctum books, 2021)
"((( is conceived of not only as a poetry collection and an artist book, but also as a series of actions, a sculpture, an installation, a living object, and a verbal ecosystem. The poetic voyage of (((, recounted in a concrete yet mysterious, abstract yet bodily language, is proposed here in a trilingual English-Italian-French edition. In the spirit of Uitgeverij's editorial approach, this will allow readers from different parts of the world to discover in their own ways how ((( explores some of the author's recurring themes through highly innovative poetic and narrative processes: the effects of war on children; technology and surveillance systems; immaterial and unknown phenomena; human emotions and non-human manifestations of nature via undefined objects and bodies, animals, and cosmological landscapes. The three parentheses of the title hint at multiple layers that are opened and never closed: ((( seeks to push language out of its verbal and human boundaries, towards unobservable territories. The genre of this book, although stemming from poetry in the sense of Dichtung, that is, concentration of meaning in highly dense verbal structures, is eminently queer, as it escapes identities and definitions. Through its multidimensional, intense, and surprising writing architecture, ((( explores new conceptual and emotional possibilities in the 21st century, confirming poetry and post-genre writing as powerful forms of inquiry in the contemporary era."